PENERAPAN MEDIA PEMBELAJARAN BERBASIS GAME BAAMBOOZLE UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA MATERI PENYAJIAN DATA DALAM BENTUK TABEL PADA PESERTA DIDIK KELAS III UPT SD NEGERI SENDANGHARJO 4 TUBAN - Rohmat Fajar Shofarin; Sumadi; Sri Wahyuni (STKIP Subang, 2026)
This classroom action research (CAR) was motivated by the low learning engagement and mathematics learning outcomes of third-grade students, particularly on the topic of presenting data in table form, at UPT SD Negeri Sendangharjo 4 Tuban. Initial observation showed a class average score of only 70 with classical learning completeness of 31.8 percent, both below the Learning Achievement Criteria (KKTP) of 78. This study aimed to describe the implementation of Baamboozle game-based learning media and to examine its effect on improving students' learning engagement and outcomes. The research used a Classroom Action Research design carried out in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 22 third-grade students of UPT SD Negeri Sendangharjo 4 Tuban in the 2025/2026 academic year. Data were collected through observation, tests, and documentation, then analyzed descriptively and quantitatively. The results showed that the implementation of Baamboozle-based learning media increased students' active engagement during the learning process, including attention, questioning, answering, discussing, and enthusiasm. Learning outcomes also improved, as shown by the increase in the class average score from 74 in Cycle I to 85 in Cycle II, while classical completeness rose from 55 percent in Cycle I to 86.4 percent in Cycle II. It can be concluded that the implementation of Baamboozle game-based learning media is effective in improving both the learning engagement and the mathematics learning outcomes of third-grade students.